A statistical programme assignment model - Jonas Staghøi; Michael Svarer; Michael Rosholm (Institute for the Study of Labor (IZA), 2007)
When treatment effects of active labour market programmes are heterogeneous in an observable way across the population, the allocation of the unemployed into different programmes becomes a particularly important issue. In this paper, we present a statistical model designed to improve the present assignment mechanism, which is based on the discretionary choice of case workers. This is done in a duration model context, using the timing-of-events framework to identify causal effects. We compare different assignment mechanisms, and the results suggest that a significant reduction in the average duration of unemployment spells may result if a statistical programme assignment model is introduced. We discuss several issues regarding the implementation of such a system, especially the interplay between the statistical model and case workers.
Keywords: J64; 330; Profiling; targeting; statistical treatment rules; heterogeneous effects; Statistische Methode; Ökonometrisches Modell; Arbeitsmarktpolitik; Arbeitsvermittlung; Persönlichkeitspsychologie; Matching; Dänemark